Left bundle branch area pacing results in more physiological ventricular activation than biventricular pacing in patients with left bundle branch block heart failure - Sussenbek, Ondrej; Rademakers, Leonard; Waldauf, Petr; Jurak, Pavel; Smisek, Radovan; Stros, Petr; Poviser, Lukas; Vesela, Jana; Plesinger, Filip; Halamek, Josef; Leinveber, Pavel; Herman, Dalibor; et al. (European heart journal supplements, 2023)
Biventricular pacing (Biv) and left bundle branch area pacing (LBBAP) are methods of cardiac resynchronization therapy (CRT). Currently, little is known about how they differ in terms of ventricular activation. This study compared ventricular activation patterns in left bundle branch block (LBBB) heart failure patients using an ultra-high-frequency electrocardiography (UHF-ECG). This was a retrospective analysis including 80 CRT patients from two centres. UHF-ECG data were obtained during LBBB, LBBAP, and Biv. Left bundle branch area pacing patients were divided into non-selective left bundle branch pacing (NSLBBP) or left ventricular septal pacing (LVSP) and into groups with V6 R-wave peak times (V6RWPT) < 90 ms and ≥ 90 ms. Calculated parameters were: e-DYS (time difference between the first and last activation in V1-V8 leads) and Vdmean (average of V1-V8 local depolarization durations). In LBBB patients (n = 80) indicated for CRT, spontaneous rhythms were compared with Biv (39) and LBBAP rhythms (64). Although both Biv and LBBAP significantly reduced QRS duration (QRSd) compared with LBBB (from 172 to 148 and 152 ms, respectively, both P < 0.001), the difference between them was not significant (P = 0.2). Left bundle branch area pacing led to shorter e-DYS (24 ms) than Biv (33 ms; P = 0.008) and shorter Vdmean (53 vs. 59 ms; P = 0.003). No differences in QRSd, e-DYS, or Vdmean were found between NSLBBP, LVSP, and LBBAP with paced V6RWPTs < 90 and ≥ 90 ms. Both Biv CRT and LBBAP significantly reduce ventricular dyssynchrony in CRT patients with LBBB. Left bundle branch area pacing is associated with more physiological ventricular activation.
Keywords: Heart failure; Ventricular synchrony; LBBAP; Biv CRT; UHF-ECG